Emprendimientos sociales en la universidad del Valle - Rodríguez Ramírez, Alfonso (Corporación Universitaria Americana, 2022)
Social entrepreneurship refers to the organizational environment in which it operates, the social enterprise, as "An organization driven by a social or environmental purpose. As in any business, the company competes to deliver goods and services. The difference is that the social purpose is at the heart of what they do, and the profits they make are reinvested towards achieving this social purpose or mission."